Analytical Solution of MHD Stagnation-Point Flow and Heat Transfer of Casson Fluid over a Stretching Sheet with Partial Slip. (5th August 2013) - Nandy, Samir Kumar
Abstract : This paper investigates the hydromagnetic boundary layer flow and heat transfer of a non-Newtonian Casson fluid in the neighborhood of a stagnation point over a stretching surface in the presence of velocity and thermal slips at the boundary. The governing partial differential equations are transformed into nonlinear ordinary differential equations using similarity transformations. The analytic solutions are developed by a homotopy analysis method (HAM). The results pertaining to the present study indicate that the flow and temperature fields are significantly influenced by Casson parameter (β ), the magnetic parameterM, the velocity slip parameterδ, and the thermal slip parameterγ . An increase in the velocity slip parameterδ causes decrease in the flow velocity, while an increase in the value of the thermal slip parameterγ causes increase in the temperature of the fluid. It is also observed that the velocity at a point decreases with increase inβ .